Easy Read On Consumer Behavior - Siti Rahayu, Binti Hussin; Siti Haslina, Binti Hussin; Salina, Binti Kassim (Universiti Putra Malaysia Press, 2018)
The study of Consumer Behaviour has never been more exciting than what has transpired in the consumer behaviour trend for at least the past 10 years. Markets all over the world have seen tremendous changes in the composition of consumers, consumers’ characteristics and more importantly, consumers’ preferences and demand. Marketers who follow their customers and who understand the factors influencing consumer purchase decisions will be the one who will successfully penetrate the dynamic markets. While those marketers and brands that use the traditional ways of marketing may lose their market grips. There are more works needs to be done in determining consumers’ needs and wants and fulfilling their demand at an ever changing global environment. Easy Read on Consumer Behavior is meant for those who are looking for a glimpse of the changes in the consumer market and consumer behavior in general. The book provides an overview of the study of consumer behaviour and a brief description on the growing new types of consumers in the world. This book discusses the concepts and models of consumer behaviour, highlighting the applications of these concepts and models into the overall framework of understanding consumer behaviour in which will leads to the development of effective marketing strategies. Although a lot has been written about consumer behaviour, this book provides a brief yet broad discussions of the changes in the market and trends in consumer behaviour that are significantly changing the strategies of marketers and brands in the world.